2016
DOI: 10.18805/ijar.9641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plantago major extract on serum protein fractions in broiler diet

Abstract: The aim of this study was to determine the effects of Plantago major’s (P.major) water extract added into broiler diets at different levels on serum protein fractions. A total of 112 Ross 308 broiler chicks were used in the study. Experiment consisted of control and 3 treatment groups with a 28 chicks within each group. Each experimental group was divided into four subgroups consisting of 4 chicks. A basal (control) diet was prepared and three experimental diets were established by addition of P.major into bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The addition of pea meal as a source of protein into broiler diets can improve carcass quality and may result in favorable lipid profile, without adversely affecting growth performance traits (Igbasan & Guenter, 1996;Pilarski et al, 2005;Laudadio et al, 2012). The broiler serum proteins and fractions can be affected by the application of different feedstaff (Bingol et al, 2016). In this study, total protein concentrations in group P20 were significantly higher than in group P40 (p<0.05).…”
Section: Discussionmentioning
confidence: 48%
“…The addition of pea meal as a source of protein into broiler diets can improve carcass quality and may result in favorable lipid profile, without adversely affecting growth performance traits (Igbasan & Guenter, 1996;Pilarski et al, 2005;Laudadio et al, 2012). The broiler serum proteins and fractions can be affected by the application of different feedstaff (Bingol et al, 2016). In this study, total protein concentrations in group P20 were significantly higher than in group P40 (p<0.05).…”
Section: Discussionmentioning
confidence: 48%
“…These compounds can well justify the reducing effects of some plants on blood sugar and lipids, as they prevent biochemical changes in blood [4]. Some medicinal herbs that contain such active compounds are: Camellia sinensis (Theaceae), which includes a significant amount of polyphenols including catechins, [5,6]; Rosa canina (Rosaceae), which contains phenolic acid, proanthocyanidins, polyphenols, unsaturated fatty acids, phospholipids, minerals, galaldipids, carotenoids and vitamin C [7,8]; Althaea officinalis (Malvaideae), containing various natural compounds such as peptin, starch, monosaccharides, dicalcium, flavonoids, antioxidants, coumarins, scopolinotine, tannin, asparagine and many amino acids [9,10]; and Plantago major (Plantaginacea) which contains alkaloids, caffeic acid derivatives, flavonoids, and iridoid glycosides [11,12]. Orlistat is a drug used for the treatment of obesity [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, differences among the groups for feed intake, body weight weekly, body weight gain and feed conversion ratio values were insignificant but the addition of 0.5% plantain in the diet had positive effect on growth, feed intake, feed conversion ratio, performance index and carcass characteristics of broilers (Chacrabati et al, 2013). In another experiment by the effects of Plantago major water extract obtained from 5, 10, 15g dried and grilled plant for per kg diet were demonstrated that addition of Plantago major extract at differing levels into broiler diet did not affected animal performance and carcass parameters (Bingöl et al, 2010). Obtaining different results in this way may result from the use of different species, different dosing and extracting methods in the studies.…”
Section: Discussionmentioning
confidence: 91%